Phase II APEC trial: The impact of primary tumor side on outcomes of first‐line cetuximab plus FOLFOX or FOLFIRI in patients with RAS wild‐type metastatic colorectal cancer. Issue 4 (15th May 2019) - Price, Timothy; Shen, Lin; Ma, Brigette; Esser, Regina; Chen, Wenfeng; Gibbs, Peter; Lim, Robert; Cheng, Ann‐Lii
Abstract: Aim: The open‐label, nonrandomized, phase II APEC study enrolled 167 patients with RAS wild‐type (wt) metastatic colorectal cancer (mCRC) to investigate the safety and efficacy of first‐line, every‐2‐weeks cetuximab plus investigator's choice of FOLFIRI or FOLFOX in this patient population. Methods: A subgroup analysis of the APEC study population by primary tumor location was performed. Results: A total of 130 patients (81.8%) had left‐sided and 29 (18.2%) had right‐sided mCRC. Median progression‐free survival (PFS), overall survival (OS) and overall response rate (ORR) were 14.0 months, 30.6 months and 68.5% for patients with left‐sided tumors and 8.9 months, 24.6 months and 51.7% for patients with right‐sided mCRC, concurring with pivotal phase III trial results. In patients with right‐sided tumors, median PFS was 15.4 months vs 8.3 months with cetuximab plus FOLFIRI vs cetuximab plus FOLFOX, respectively; median OS was 32.1 months vs 21.8 months with cetuximab plus FOLFIRI vs cetuximab plus FOLFOX, respectively. Conclusion: The APEC tumor‐location subgroup analysis results were largely consistent with available literature regarding the equivalent efficacy of cetuximab plus FOLFIRI/FOLFOX in patients with left‐sided RAS wt mCRC. A trend toward improved efficacy with cetuximab plus FOLFIRI compared with cetuximab plus FOLFOX was observed in patients with right‐sided tumors; however, a direct comparison between groups cannot be made due to the nonrandomized study design. Nevertheless, the similar ORR observed with either chemotherapy backbone in patients with right‐sided RAS wt mCRC suggests a potential role for both regimens in this patient population when cytoreduction is a treatment goal.